The Effects Of Minimum Wage And Gross Regional Domestic Product (GRDP) On Employment In East Java - Rahmi, Ita Azizah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
This paper aimed to analyze what variables give influence towards employment. The independent variables used in this study were minimum wage and Gross Regional Domestic Product. This study used a secondary annual time-series data from 2009 to 2013. The method used in this study was panel data regression with the approach of Fix Effect Model. The result of this study showed that minimum wage is significant towards employment while Gross Regional Domestic Product is insignificant towards employment. Both are negative impact towards employment. The result also showed that minimum wage is more dominant in influencing the employment.Keywords : Employment, Minimum Wage, GRDP